International Migration and the Distribution of Income in New Zealand Metropolitan and Non-Metropolitan Areas - Omoniyi Alimi; David C. Maré; Jacques Poot (Institute of Labor Economics (IZA), 2018)
Since the 1980s, income inequality in New Zealand has been a growing concern - particularly in metropolitan areas. At the same time, the encouragement of permanent and temporary immigration has led to the foreign-born accounting for a growing share of the population; this is disproportionally so in metropolitan areas. This paper investigates the impact of immigration, by skill level and length of stay, on the distribution of income in metropolitan and non-metropolitan areas. We apply decomposition methodologies to data obtained from the 1986, 1991, 1996, 2001, 2006 and 2013 Censuses of Population and Dwellings. We find that increases in the immigrant share of population in an area have an inequality-increasing and area-specific effect. Changes in immigrant-group-specific distributions of income are inequality reducing in non-metropolitan areas but inequality increasing in metropolitan areas. Inequality increased in metropolitan areas because the overall inequality-increasing effect of immigration is larger than the inequality-reducing changes for the New Zealand-born. The opposite is the case in non-metropolitan areas: the overall inequality-reducing change in the income distribution of the New Zealand born there is larger than the inequality-increasing effect of immigration. The methodologies adopted here can also benefit the study of income distribution changes in countries with similar immigration policies, such as Australia and Canada.
Keywords: D63; F22; J15; R23; 330; New Zealand; income inequality; international migration; metropolitan areas; decomposition methods